Dynamic Mechanical Loading Enhances Functional Properties of Tissue-Engineered Cartilage Using Mature Canine Chondrocytes - Bian, Liming (Mary Ann Liebert, Inc., 2010)
OBJECTIVE: The concept of cartilage functional tissue engineering (FTE) has promoted the use of physiologic loading bioreactor systems to cultivate engineered tissues with load-bearing properties. Prior studies have demonstrated that culturing agarose constructs seeded with primary bovine chondrocytes from immature joints, and subjected to dynamic deformation, produced equilibrium compressive properties and proteoglycan content matching the native tissue. In the process of translating these results to an adult canine animal model, it was found that protocols previously successful with immature bovine primary chondrocytes did not produce the same successful outcome when using adult canine primary chondrocytes. The objective of this study was to assess the efficacy of a modified FTE protocol using adult canine chondrocytes seeded in agarose hydrogel and subjected to dynamic loading. METHOD: Two modes of dynamic loading were applied to constructs using custom bioreactors: unconfined axial compressive deformational loading (DL; 1 Hz, 10% deformation) or sliding contact loading (Slide; 0.5 Hz, 10% deformation). Loading for 3 h daily was initiated on day 0, 14, or 28 (DL0, DL14, DL28, and Slide14). RESULTS: Constructs with applied loading (both DL and Slide) exhibited significant increases in Young's modulus compared with free-swelling control as early as day 28 in culture (p < 0.05). However, glycosaminoglycan, collagen, and DNA content were not statistically different among the various groups. The modulus values attained for engineered constructs compare favorably with (and exceed in some cases) those of native canine knee (patella groove and condyle) cartilage. CONCLUSION: Our findings successfully demonstrate an FTE strategy incorporating clinically relevant, adult chondrocytes and gel scaffold for engineering cartilage replacement tissue. These results, using continuous growth factor supplementation, are in contrast to our previously reported studies with immature chondrocytes where the sequential application of dynamic loading after transient transforming growth factor-β3 application was found to be a superior culture protocol. Sliding, which simulates aspects of joint articulation, has shown promise in promoting engineered tissue development and provides an alternative option for FTE of cartilage constructs to be further explored.